The Effect Of Handouts Based On Project-Based Learning Equipped With Portfolio Assessment On The Learning Outcomes Of Students In Class XI SMA N 13 Padang - Al Irsyat, Tomy; Satria Dewi, Wahyuni; Hidayati, Hidayati; Hidayat, Rahmat (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2023)
The research motivation is the low outcomes of learning in physics students at SMA N 13 Padang because learning is still focused on the teacher, the teacher has not used a learning model that makes students active in learning, handout materials for teaching are rarely used by teachers in the process of learning and the assessment carried out is still not carrying out authentic and overall assessment. The solution used is to apply project-based learning-based handouts equipped with portfolio assessment to increase outcomes of learning in physics of students. This research purposes is to see whether there is a positive impact of applying project-based learning-based handouts equipped with portfolio assessments on the learning outcomes of SMA N 13 Padang students. The research type conducted is a pseudo-experiment with a design for research Randomized Posstest Only Control Group Design. The population for research were total students of class XI Phase F SMA N 13 Padang who were enrolled in the 2023/2024 school year. Sampling was conducted using technique of Cluster Random Sampling. The samples of this research were class XI F3 as the class for experimental and class XI F4 as the class for control with the same number of class members. The research data includes student outcomes of learning in physics in the aspect of knowledge (cognitive). The research instrument was a learning outcome test. The technique for data analysis used is test of normality, homogeneity and hypothesis at the real level of 0.05. According on analysis of data, the average outcomes of learning in physics of students in the knowledge aspect in the class for experimental is 76 higher than the class for control which is 67. Hypothesis testing of the posstest conducted th < tt where 2.294 < 1.666 so the result is reject for H0 and accept for H1, so the conclusion that in the research the effect of project-based learning-based handouts equipped with portfolio assessment has a positive impact on the outcomes of learning in physics of students in class XI Phase F SMA N 13 Padang on the knowledge aspect with a real level of 0.05.